Turpilóquio em português e italiano: reflexões sobre marcas de uso de itens tabus em dicionários - Orsi, Vivian [UNESP]; Bueno, Matheus dos Santos [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2014)
In this paper, we tried to understand the place of taboo words and their importance in the language. We focused questions about the taboo and how words can be prohibited. We elected swear words as our object of research because these words have an important place in the lexicon of many speakers, and they are present in books and movies, as well as in the everyday speech. Therefore, we tried to show that they must be analyzed with attention and also free from prejudices. We found out that the use of bad words can be very different in the languages selected and they reflect thus the culture of the languages involved.

Neste artigo procuramos compreender o lugar das palavras tabuizadas e sua importância na língua. Focamos questões sobre o tabu e sobre como as palavras podem ser proibidas. Elegemos como objeto de pesquisa os palavrões pois observamos que essas palavras ocupam um importante espaço no léxico de muitos falantes, e estão presentes em livros e filmes, além da fala cotidiana. Assim tentamos mostrar que devem ser analisados com atenção e livres de preconceitos. Verificamos que os palavrões podem ser muito diferentes nas línguas selecionadas, refletindo, desse modo, a cultura dos idiomas envolvidos.
Swear words in Portuguese and Italian: reflections on the usage labels of taboo items in dictionaries
Keywords: Lexicologia; Dicionários; Turpilóquio; Lexicology; Dictionaries; Swear words